Examination of January, December and November Effects on the Indian Stock Market - Mehta, Kiran; Chander, Ramesh (Indian Journal of Finance, 2010)
It was three decades back (1976) when Rozeff and Kinney documented the evidences of higher returns in the month of January in comparison to other months over the US stock market. And after that, various studies identified the mixed evidences of January Effect on the stock market world over. A vast literature is available giving multi explanation of January effect in various capital markets the world over. The fittest explanation for the January effect in most of the capital market was related with the tax-loss selling hypothesis. December is found to be at the end of the financial year in some countries and the investors set off their loss through the capital gains on other avenues and regain their position in the month of January, which causes further gushes in the market movements in the month of January and smart investors can earn abnormal returns by waiting for some time and opt to sell strategies in the month of January as the returns in this month are comparatively high. Most of the studies in this context were conducted on American and European Markets. No strong evidences have been found for the January Effect in the countries where the financial year starts in the month other than January. Jacobs and Kenneth (1988) identified that the stocks earned higher returns as well as higher risk premium in the month of January, especially in the case of small stocks. But the Indian market has not witnessed January effect as in India, the financial year ends in the month of March. But some other months have depicted the anomalous pattern in the distribution of stock indices returns during various months of the year (Chatterji and Maniam, 1997, Pandey 2002, Raj and Damini, 2006 etc.). So, the present study has been destined to examine the possible existence of the January Effect and in consideration of the past findings, the anomalous behavior of the stock index return series has also been examined in the month of December and November. Any kind of inconsistency in the behavior of the return series of the stock indices resulting due to these effects may result in profitable opportunity for the investors and fund managers. So, if some strong evidences could be obtained through the present study for such anomalous patterns in the market behavior, then it may raise a question on the strong arguments developed in favor of increased efficiency over the Indian stock market during the past years.